Neuroforum : Organ der Neurowissenschaftlichen Gesellschaft (De Gruyter, 2017)
Neuroforum publishes invited review articles from all areas in neuroscience. The readership includes besides basic and medical neuroscientists, practicing physicians, school teachers, students and journalists. Besides the review articles, Neuroforum publishes short reports on new methods and developments in neurosciences, on research institutes, research groups and programs, book reviews and the newsletter of the German Neuroscience Society.